Determination of the Spectral Properties and Harmonic Levels for Driving an Induction Motor by an Inverter Driver under the Different Load Conditions - Taskin, S.; Gokozan, H. (Elektronika ir Elektrotechnika, 2011)
This paper analyses the electrical power quality for the induction motor of 75 kWusing the spectral analysis methods. Measurements are carried out by collecting the current and voltage variations in a ceramic factory. Spectral analyzing techniques are applied to the collected data to get the spectral properties. Hence, induction motor operation regions are categorized under three zones. These are no-load condition; transient case from no-load to load and full-load, respectively. Consequently, the variations of the harmonics are compared with each other under these different operation conditions and then the most important characteristics of the harmonics are determined. In this manner, dominant harmonics are obtained as 5th, 7th, 11th, 13th and 17th harmonics as well as fundamental frequency at 50 Hz. Ill. 9, bibl. 18, tabl. 1 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.108.2.149